Fabric for Fashion: The Complete Guide: Natural and Man-made Fibers - Clive Hallett; Amanda Johnston (London Laurence King Publishing, 2014)
Fabric For Fashion: The Complete Guide is the only book specifically for fashion designers to explain the behavior and properties of different fabrics. Fashion design is largely determined by how the fabrics work, move, feel and look. The most successful fashion designers are those who understand their materials, who match design skill with technical knowledge. This book bridges that gap by providing a mix of practical information and industry vocabulary, visually examining generic fabric types, discussing the characteristics of fabrics and showing how to exploit materials to push the boundaries of design. With stunning color photographs that show how fashion designers, both past and present, have worked with fabrics, the book's prime objective is to stimulate creative exploration of the relationship of fabrics to fashion.
Keywords: Fashion; Fashion design; Sewing; Design; Art; Nonfiction; (FSD111) Introduction to Fashion Product (Workshop)